Effect of Priming on Brassica rapa subsp. chinensis (Bok Choy) Seeds Germination - Chooi Lin Phooi; Elisa Azura Azman; Roslan Ismail (agriTECH, 2023)
Brassica rapa subsp. Chinensis, commonly known as Bok Choy, is a nutrient-rich vegetable with substantial antioxidant content. Therefore, this study aimed to evaluate the effect of hydropriming and bio-nutri-priming using Sandwich compost leachate on seed germination, SPAD reading, and dry matter accumulation in 280 dwarf variants of Bok Choy seeds sourced from Green Eagle. The experimental process involved hydropriming with tap water, bio-nutri-priming using 0.2% Sandwich compost leachate, and a control group cultivated in soil without priming. A complete randomization design (CRD) with three replications assessed seed germination performance, SPAD, root and shoot dry matter, and root-to-shoot ratio. While there was no significant difference in the germination percentage (88.35±1.13%), the entire priming seeds exhibited a 2-day peak germination period, compared to 3 days for the non-priming counterparts. Bio-nutri-priming seeds showed faster median and mean germination times due to enhanced nutrient uptake. They further displayed high SPAD readings, suggesting a lack of toxic compounds. The dry matter production of all treated Bok Choy was similar because administered treatments did not interfere with plant growth and development. Therefore, applying bio-nutri-priming using Sandwich compost leachate positively affected seed germination performance, warranting its recommendation as a seeds priming solution.